Liquid-solid separation method
By using cationized cellulose with high charge density and performing process shear force treatment in high shear steps, the problems of low flocculation efficiency and non-degradable materials in liquid-solid separation in the prior art are solved, and efficient solid fractions and a more sustainable process are achieved.
Patent Information
- Application Number
- CN202380065721.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-20
- Filing Date
- 2023-09-19
- Publication Date
- 2025-04-08
AI Technical Summary
The petroleum-based synthetic cationic polymers used in the liquid-solid separation process are non-degradable, making it difficult to achieve sustainable treatment of solid fractions, and have low flocculation efficiency.
Cationic cellulose with high charge density and appropriate salt viscosity is employed and processed shearing in a high shear step to contact solid particles in the suspension to achieve flocculation.
The solid content after liquid-solid separation is improved, the dehydration time is shortened, the performance of flocs is improved, and more efficient liquid-solid separation is achieved.
Abstract
Description
Technical Field
[0001] The present invention relates to a method for flocculating solid particles in liquid-solid separations according to the preamble of the attached independent claim. Background Art
[0002] Many industrial processes include a liquid-solid separation step, in which solid particles are separated from a liquid phase. Typically, a suspension of solid material suspended in an aqueous continuous phase is subjected to a liquid-solid separation to provide a solid fraction and a liquid fraction that can be further processed. For example, a liquid-solid separation step is used in water treatment processes, in the manufacture of pulp, paper, paperboard, etc., and in the mining industry. A typical example of a liquid-solid separation step is the dewatering of sludge in any water treatment process. Sludge typically includes various solid particles and / or microorganisms suspended in an aqueous phase. In the liquid-solid separation step, the water content of the sludge is reduced so that the solid fraction of the sludge can be further processed, such as deposited, used as a fertilizer, or incinerated for energy production.
[0003] The liquid-solid separation step usually includes flocculation of solid particles suspended in the liquid phase. Flocculation and / or coagulation chemicals are used to improve the formation and / or quality of the flocs formed. For example, in water treatment processes, sludge can be conditioned by adding flocculants (inorganic compounds such as iron and lime, or synthetic organic polymers) before the dewatering step. These flocculants are added to sludge to improve sludge handling and increase the dewatering effect in liquid-solid separation.
[0004] Cationic polymers are often used as flocculants in liquid-solid separation. Cationic polymers used as flocculants are usually petroleum-based synthetic polymers. Due to the non-degradability of synthetic polymers, when synthetic cationic polymers are used in the liquid-solid separation step, the separated solid fraction obtained from wastewater treatment may not be used for landfill, composting or soil improvement. In addition, there is currently a growing trend towards more sustainable industrial processes and bio-based and / or biodegradable chemicals. This desire to use bio-based and / or biodegradable chemicals has aroused great interest in finding alternatives to petroleum-based synthetic cationic polymers. An interesting alternative is cationized cellulose, because cellulose itself is abundant, renewable and biodegradable. Cationized cellulose and cationized cellulose derivatives have been tested as flocculants, for example in wastewater treatment, as described in Sievänen et al., Cellulose (2015), 22, 1861-1872. However, there is still a need to find new methods for improving flocculation efficiency in liquid-solid separation processes. Summary of the invention
[0005] It is an object of the present invention to minimize or even eliminate the disadvantages existing in the prior art.
[0006] The object of the present invention is also to provide a more sustainable flocculation method in a liquid-solid separation process, in particular a sludge dewatering method in a water treatment process.
[0007] Other objects of the present invention are to provide a process which provides efficient flocculation and high solids content of the separated solids after the liquid-solid separation step.
[0008] These objects are achieved by the invention having the features presented below in the characterizing part of the independent claim. Some preferred embodiments are disclosed in the dependent claims.
[0009] The embodiments mentioned herein relate, where applicable, to all aspects of the invention, even if this is not always mentioned individually. DETAILED DESCRIPTION
[0010] According to the present invention, a typical method for flocculating solid particles in a liquid-solid separation process comprises:
[0011] - obtaining a cationized cellulose having a charge density of at least 1.5 meq / g dry matter measured at pH 4 and a 2% salt viscosity of at least 50 mPas;
[0012] - subjecting the cationized cellulose at process concentration to a process shear force in a high shear step, wherein the process shear force corresponds to or is greater than a default shear force that increases the 2% salt viscosity of the cationized cellulose by at least a factor of 2;
[0013] - contacting the cationized cellulose with a suspension of solid particles suspended in a continuous aqueous phase after the high shear step and flocculating the solid particles; and
[0014] - Separation of flocculated solid particles from the continuous aqueous phase in a dewatering step.
[0015] It has now surprisingly been found that when a cationized cellulose solution having a charge density of at least 1.5 meq / g is subjected to appropriate process shear forces, the flocculation ability of the cationized cellulose is improved in an unexpected manner. This improvement in flocculation ability may manifest itself in high solid contents after liquid-solid separation, short dewatering times and / or improved floc properties, such as floc strength, generally providing more efficient liquid-solid separation. The theoretical background for the observed phenomenon is not yet fully understood, but it is speculated that the shear forces may open up the structure of the dissolved cationized cellulose and influence its interaction with solid particles during the flocculation process.
[0016] The high shear step is an important feature of the present invention. The cationized cellulose in solution should be subjected to an appropriate process shear force in the high shear step. It has been found that the appropriate process shear force corresponds to a default shear force that increases the 2% salt viscosity by at least 2 times. In this context, the term "2% salt viscosity" refers to the apparent viscosity value measured at 25°C in an aqueous system consisting of 1.8 wt-% concentration of dissolved or dispersed cationized cellulose, water and 9.1 wt-% dissolved NaCl. The salt viscosity value is measured using a Brookfield LV viscometer (spindle #18 or #31) with a small sample adapter, using the maximum possible rotation speed. The multiple is calculated by dividing the 2% salt viscosity value of the cationized cellulose solution after high shear treatment by the 2% salt viscosity value of the same cationized cellulose solution after dissolving the cationized cellulose without high shear treatment. It is assumed that the increase in the 2% salt viscosity value reflects the change in the three-dimensional structure of the cationized cellulose in the solution, thereby providing a reliable parameter for determining the appropriate shear force required. The conditions for generating the appropriate shear forces are defined such that when they are applied to a cationized cellulose solution, the 2% salt viscosity of the cationized cellulose solution is at least twice the 2% salt viscosity of the same cationized cellulose solution that has not been subjected to high shear. Once the appropriate shear conditions are determined, they can be applied to cationized cellulose solutions of any concentration.
[0017] According to a preferred embodiment of the present invention, the cationized cellulose solution can be subjected to a process shear force corresponding to a default shear force in the high shear step, which default shear force increases the 2% salt viscosity by 2-50 times, preferably 2-40 times, more preferably 2-23 times or 5-30 times.
[0018] At process concentrations, the cationized cellulose solution may be subjected to process shear forces in any suitable high shear device or high shear apparatus capable of generating appropriate process shear forces in an aqueous system. Preferably, the cationized cellulose is subjected to process shear forces in a high shear step performed at atmospheric pressure (101.3 kPa). For example, the cationized cellulose solution may be subjected to process shear forces in a homogenizer, a high-speed mixer, a disperser, a rotor-stator mixer, a mixer having two counter-rotating rotors, a centrifugal pumping device providing a direct current or back-rotating flow, a shear pump, and the like. In some cases, ultrasonic treatment is applicable. Suitable high shear mixing devices and homogenizers are well known to those skilled in the art and are commercially available, for example under the trade names Ultra Turrax®, Polytron®, Atrex®, Silverson®, Ystral®, Cavitron™, and Waukesha shear pumps™. For example, the cationized cellulose may be dissolved in water, and then the process shear forces are applied to the obtained cellulose solution by high shear homogenization, and then the cellulose solution is contacted with an aqueous suspension containing solid particles to be flocculated. For example, high shear homogenization can be achieved by using a rotation speed of at least 2000 rpm. Homogenization is preferably carried out as a mechanical homogenization without using a pressure difference, for example in a homogenizer using the rotor-stator principle. Appropriate process shear forces can also be achieved in a shearing step, wherein the cationized cellulose solution is subjected to process shear forces by means of a centrifugal pump or the like, for example during pumping after the cationized cellulose is dissolved or dispersed in water.
[0019] Before the cationized cellulose solution is contacted with the suspension to be flocculated, the solution of cationized cellulose is subjected to process shear forces in order to take full advantage of the improved flocculation effect. After the high shear step, in which the cationized cellulose solution has been subjected to process shear forces, the cationized cellulose solution is contacted with an aqueous suspension containing solid particles. The solid particles suspended in the continuous aqueous liquid phase of the suspension are flocculated. The flocculated solid particles are then separated from the continuous aqueous phase of the suspension in a dewatering step. The separation of the flocculated solid particles can be carried out, for example, by using gravity settling, filtration, pressing or centrifugal force. Various mechanical dewatering devices, such as centrifuges, belt presses or box presses, preferably centrifuges, can be used to separate the aqueous phase from the formed flocs containing solid particles.
[0020] The cationized cellulose is obtained and used in the present invention in the form of an aqueous solution. The cationic cellulose is in the form of a solution before and after the high shear step and there is no gel formation. The cationized cellulose solution can be obtained at a suitable process concentration, or it can be diluted to a suitable process concentration before the high shear step. If the cationized cellulose is initially in the form of solid particles, it is preferably dissolved in water and optionally diluted to obtain a cationized cellulose solution with a suitable process concentration. Suitable process concentrations can be, for example, in the range of 0.1-5 wt-%, preferably 0.15-3 wt-%, more preferably 0.2-1 wt-%. Typically, the cationized cellulose suitable for the present invention is at least partially water-soluble. Preferably, the cationized cellulose is water-soluble.
[0021] In the present context, the term "water-soluble" means that the cationized cellulose is completely miscible with water, providing a clear or nearly clear solution. When mixed with excess water, the cationized cellulose dissolves, and the solution of cationized cellulose obtained is preferably substantially free of discrete solid particles, fibers, fibrils, particles or coagulated aggregates of the cationized cellulose. Excess water means that the solution obtained is not a saturated solution.
[0022] Since the cationized cellulose suitable for use in the present invention is at least partially water-soluble or water-soluble, the high shear step preferably does not involve the formation of fibrils, such as the formation of nanocellulose or the like. Preferably, the high shear step is carried out in a manner that does not cause structural degradation or shortening of the cellulose molecules. Preferably, at least 70%, or at least 80%, or at least 90% of the cellulose molecules have the same structural length before and after the high shear step. On the contrary, it is presumed that the high shear step causes the structure of the dissolved cellulose molecules to open or unravel themselves, so that the cationic groups of the cationized cellulose can more easily interact with each other.
[0023] When measured before high shear treatment, the cationized cellulose solution may have a 2% salt viscosity of at least 80 mPas, preferably at least 100 mPas, more preferably at least 150 mPas. According to one embodiment, the 2% salt viscosity of the cationized cellulose solution measured before high shear treatment may be in the range of 80-10000 mPas, preferably 100-10000 mPas, more preferably 150-6000 mPas, even more preferably 200-2500 mPas.
[0024] According to a preferred embodiment, the method for flocculating solid particles in a liquid-solid separation process comprises:
[0025] - obtaining a suspension of solid particles suspended in a continuous aqueous phase;
[0026] - obtaining a cationized cellulose having a charge density of at least 1.5 meq / g dry matter measured at pH 4 and a 2% salt viscosity of at least 50 mPas;
[0027] - subjecting the cationized cellulose at process concentration to a process shear force in a high shear step, wherein the process shear force corresponds to or is greater than a default shear force that increases the 2% salt viscosity of the cationized cellulose by at least a factor of 2;
[0028] - contacting the cationized cellulose with the suspension of solid particles after the high shear step and flocculating the solid particles; and
[0029] - Separation of flocculated solid particles from the continuous aqueous phase in a dewatering step.
[0030] Cationized cellulose suitable for use in the present invention has a charge density of at least 1.5 meq / g dry matter measured at pH 4. The charge density values are given per gram of cationized cellulose material in the form of dry matter and are determined at pH 4 by using a particle charge titrator (AFG Analytic GmbH, Germany). According to a preferred embodiment, the cationized cellulose may have a charge density of at least 1.75 meq / g dry matter, preferably at least 2 meq / g dry matter. According to one embodiment, the charge density of the cationized cellulose may be in the range of 1.5-4 meq / g dry matter, preferably 1.75-3.75 meq / g dry matter, more preferably 2-3.5 meq / g dry matter. It is assumed that the high charge density of the cationized cellulose interacts strongly with the solid particles of the suspension, especially after a high shear step. The high charge density of the water-soluble cationized cellulose may also increase the strength of the formed flocs, which can resist floc breaking forces even in harsh environments, such as during dewatering by centrifugation. This improves the results of liquid-solid separation.
[0031] According to one embodiment, the cationized cellulose can have a degree of substitution DS of at least 0.32, preferably at least 0.37, sometimes even at least 0.4 or at least 0.5. The degree of substitution can be in the range of 0.32-1.75, preferably 0.37-1.6, more preferably 0.4-1.5 or 0.5-1.3. According to one embodiment, the degree of substitution is at least 0.6, at least 0.7 or at least 0.8, for example in the range of 0.6-1.75, 0.7-1.6 or 0.8-1.5. The degree of substitution can be calculated according to the measured charge density value of the cationized cellulose obtained. The degree of substitution provides an estimate of the number of cationic groups of the anhydroglucose unit of each cellulose. It is assumed that a high degree of substitution increases the water solubility of the cationized cellulose and makes it more suitable for shearing treatment.
[0032] The charge density of the cationized cellulose is generally related to the degree of substitution of the cationized cellulose material and vice versa. An example of the correspondence between charge density and calculated degree of substitution is given in Table 1.
[0033] Table 1 Charge density and calculated degree of substitution
[0034] Charge density meq / g Calculated DS Charge density meq / g Calculated DS 0.50 0.10 2.50 0.66 0.75 0.14 2.75 0.77 1.00 0.19 3.00 0.90 1.25 0.25 3.25 1.04 1.50 0.31 3.50 1.21 1.75 0.38 3.75 1.41 2.00 0.46 4.00 1.66 2.25 0.56
[0035] The cationized cellulose suitable for use as a flocculant in the present invention may have a turbidity of less than 1000 NTU, preferably less than 500 NTU, more preferably less than 250 NTU, particularly when the cationized cellulose is derived from cellulose pulp. The turbidity may be, for example, 40-1000 NTU, 40-500 NTU or 40-250 NTU. The turbidity value is measured from an aqueous solution of the cationized cellulose at a concentration of 1 weight-% by using a HACH, 2100 AN IS laboratory turbidimeter. The low turbidity value of the cationized cellulose solution indicates that, at the process concentration, the cationized cellulose is almost completely or completely water-soluble. Preferably, the turbidity value of the cationized cellulose remains substantially unchanged before and after the high shear treatment.
[0036] Cationized cellulose can be obtained by any method for producing water-soluble cellulose with sufficient cationicity. PCT / FI2020 / 050817 discloses a possible method for preparing cationized cellulose. According to this preferred embodiment, cationized cellulose can be obtained by mixing a cellulose starting material with an alkaline liquid medium containing an organic liquid to prepare a reaction slurry, wherein the concentration of the cellulose starting material in the reaction slurry is at least 20 weight-%. The alkaline liquid includes at least one alkaline agent, at least one organic liquid and water. The alkaline agent can be selected from the group consisting of: alkali metal hydroxides, such as NaOH, LiOH or KOH; alkali metal carbonates, such as Na2CO3 or K2CO3; ammonium hydroxide; quaternary ammonium hydroxide and tetramethylguanidine. The amount of alkaline agents such as NaOH can be in the range of 7-18 weight-%, for example 7.5-15 weight-%, calculated according to the total weight of the slurry. The organic liquid can be selected from the group consisting of: secondary or tertiary alcohols, such as isopropanol, tert-butyl alcohol, sec-butyl alcohol or any mixture thereof, preferably isopropanol or isopropanol. The amount of organic liquid may be in the range of 30-55 wt-%, preferably 35-50 wt-%, more preferably 40-45 wt-%, calculated on the total weight of the pulp. After the alkalization step at a mercerization temperature of -15°C to +20°C, preferably -10°C to +10°C, more preferably -5°C to +5°C, a cationizing agent is added to the reaction pulp, preferably under an inert atmosphere, and allowed to interact with the cellulose. The cationizing agent may be selected from (3-chloro-2-hydroxypropyl)trimethylammonium chloride (CHPTAC), glycidyltrimethylammonium chloride (GTAC) or any mixture thereof. The reaction temperature during the cationization step may be <100°C, preferably in the range of 35-80°C, more preferably 40-60°C.
[0037] Cationized cellulose can be produced from any cellulose starting material selected from wood or other cellulose-containing biomass. Cationized cellulose can be produced from a cellulose starting material selected from wood or wood-based cellulose materials, which can be derived from hardwood or softwood or a mixture thereof, or from cellulose-containing biomass, such as cotton, or from agricultural and / or harvested cellulose-containing plant residues.
[0038] The present invention is applicable to flocculating solid particles in any liquid-solid separation process, wherein the solid particles are separated from the aqueous liquid phase. For example, the present invention is particularly applicable to treating wastewater, preferably municipal wastewater or industrial wastewater, or for regulating drinking water. According to a preferred embodiment, the liquid-solid separation process can be a sludge dewatering step of a water treatment process, such as a sludge dewatering step of a municipal wastewater treatment process or an industrial wastewater treatment process. The aqueous suspension to be dewatered may be municipal wastewater sludge or agricultural sludge, or it may come from a biological treatment process for wastewater and / or sewage. Alternatively, the aqueous suspension may come from an industrial process, in particular a wastewater treatment of an industrial process, or from food or beverage production or from food or beverage processing.
[0039] The aqueous suspension comprises a continuous aqueous liquid phase and organic and / or inorganic solid materials and / or particles suspended in the aqueous liquid phase. The suspension may be rich in bacteria-derived materials, particularly if it originates from a water treatment process. The aqueous liquid phase of the suspension may also contain dissolved organic matter, such as polysaccharides, humus and fatty acids. The suspension may have a biological oxygen demand (BOD) of >50 mg / l, a chemical oxygen demand (COD) in the range of 15-45 g / l, preferably 20-40 g / l, and / or a dry solid content in the range of 5-80 g / l, preferably 10-60 g / l, more preferably 20-55 g / l. The pH of the suspension may be in the range of pH 6 to pH 9, preferably pH 7 to pH 8. The conductivity of the suspension may be in the range of 5-14 mS / cm, preferably 5-10 mS / cm, and / or the charge density may be in the range of -5.5 to -1.5 μeq / g, preferably -5.0 to -1.8 μeq / g. The total phosphorus value of the suspension may be in the range of 400-1400 mg / l, preferably 450-1200 mg / l, and / or the total nitrogen value may be in the range of 1.2-3.5 g / l, preferably 1.5-3.0 g / l.
[0040] If the present invention is used in a wastewater treatment process, in particular a sludge dewatering step, the cationized cellulose solution may be contacted with the suspension in an amount of 1-30 kg / ton of dry suspension, preferably 2-20 kg / ton of dry suspension, more preferably 3-15 kg / ton of dry suspension.
[0041] According to one embodiment of the present invention, the embodiment can be used to improve the liquid-solid separation process in paper or paperboard manufacturing, such as the initial dewatering step. The cationized cellulose solution can be used as a retention enhancer or fixative and can be added to the pulp or fiber raw material to flocculate at least some of the solid components of the pulp or fiber raw material. For example, the cationized cellulose may be able to attach and / or associate hydrophobic substances to the fibers and thus to the cellulose fiber web, thereby reducing the accumulation and deposition of hydrophobic substances on process surfaces and / or water.
[0042] In the present context, the term "hydrophobic substances" includes all hydrophobic interfering substances present in the manufacture of paper, paperboard, etc., including stickies and pitches that may cause deposition. The term "stickies" means synthetic hydrophobic substances, for example derived from adhesives, printing inks, coating adhesives, such as synthetic latexes, waxes, and hydrophobic internal and surface sizing agents. The term "pitch" means natural hydrophobic substances and wood extracts, such as terpenes, sterols, sterol esters, fatty acids and their esters, resin acids and their esters, including their salts and other forms thereof.
[0043] According to one embodiment, after the high shear step, the cationized cellulose solution can be added to the crude fiber raw material containing cellulose fibers. In the context of the present application, the crude fiber raw material is understood as a fiber raw material having a fiber consistency of at least 10 g / l, preferably at least 20 g / l, more preferably at least 30 g / l. The fiber consistency can be in the range of 10-60 g / l, preferably 20-50 g / l, more preferably 30-40 g / l. Cationized cellulose can be added to the crude fiber raw material in all conventional application locations, where fixatives and / or retention aids are usually applied to the raw material. The addition of cationized cellulose can be carried out after the raw material storage tower, but before the crude fiber raw material is diluted with short-circuit clean water in the wire pit (off-machine silo). According to one embodiment, the cationized cellulose may be added to the raw material in an amount of 100-2000 g / ton, typically 200-1500 g / ton, more typically 500-1500 g / ton, given as dry matter per ton of fiber web produced.
[0044] experiment
[0045] Some non-limiting embodiments of the invention are disclosed in the following examples.
[0046] Example 1: Preparation of cationized cellulose
[0047] High molecular weight dissolving pulp refined to 30° SR was used as raw material. The pulp was predried to a dry content of 90.6 wt-% in a 6-liter Lödige DVT 5 reactor equipped with a mechanical mixer and a temperature-controlled jacket. The temperature in the jacket was set to 105°C using a thermostatic bath circulating a heating / cooling medium liquid.
[0048] The sodium hydroxide solution and isopropanol (IPA) were cooled in a refrigerator at least overnight. 347 g of predried dissolving pulp with a dry content of 90.6 wt-% (314 g, calculated as dry cellulose) were added to the Lödige reactor. The temperature of the reactor jacket was set to 0°C. Before adding to the reactor, 275 g of 40 wt-% sodium hydroxide solution and 376 g of isopropanol were mixed together. The reaction mixture was mixed for 21.3 h, 100 rpm, temperature 0°C.
[0049] (3-Chloro-2-hydroxypropyl) trimethylammonium chloride solution (CHPTAC, Sigma-Aldrich, 60 weight-% active substance) was cooled in a refrigerator. 512 g of CHPTAC was weighed into a beaker and pumped into a reactor containing an intermediate product previously reacted with sodium hydroxide at a rate of 1 l / h. During the CHPTAC feed, mixing continued and the temperature in the reactor jacket was maintained at 10 ° C. At the end of the CHPTAC feed, the temperature of the reactor jacket was raised to 60 ° C. After all CHPTAC feeds, an additional dose of 100 g of isopropanol was pumped through the same tube at the same rate to flush all CHPTAC into the reactor. After all solutions were in the reactor and the temperature of the bath reached 60 ° C, the lid of the reactor was closed, and a nitrogen stream was started to be passed into the reactor at 1 l / min. The reaction time was calculated at this time. The reaction lasted 23 hours.
[0050] At the end of the reaction, a portion of the reaction mass was taken out of the reactor for purification. The taken out portion of the reaction mass was dissolved in water in a ratio of 1:8 (reaction mass to water) and mixed with a magnetic stirrer for 15 min. After that, the pH value of the solution was lowered to pH 4.3-6.5 using 50 weight-% acetic acid. The solution was then poured into isopropyl alcohol (IPA) in a ratio of 1 g of dissolved reaction mass to 50 ml of IPA. The solution was filtered using a black belt filter paper. The filter cake was washed three times. In the two first washes, a washing liquid IPA / water 70 / 30 (by volume) was used. The last wash was performed by using a washing liquid IPA / water 80 / 20 (by volume). The washing was performed by dispersing the filter cake in the washing liquid in a ratio of 1:10 "filter cake to washing liquid" for 15 minutes. The mixture was filtered using a black belt filter paper. The last filter cake was dried overnight at 60°C. This sample was named sample A.
[0051] The obtained cationized cellulose was characterized as follows.
[0052] Charge density
[0053] Charge density at pH 4 was determined using an AFG Analytics particle charge titrator. Cationized cellulose samples were dissolved in deionized water as 0.025-0.05 weight-% solutions, the pH was adjusted to 4.0 with 0.1 M acetic acid, and titrated using 0.001 N sodium polyvinyl sulfonate (PES-Na) solution as titrant. During the titration, the pH typically increased by 0.1-0.2 pH units. Charge density is expressed as meq / g dry matter. Cationized cellulose sample A had a charge density of 1.8 meq / g dry sample.
[0054] 2% salt viscosity
[0055] The 2% salt viscosity of a cationized cellulose solution in water in the presence of salt was determined at 25°C using a Brookfield LV viscometer with a small sample adapter (using spindle #18 or #31), depending on the viscosity level. The 2% salt viscosity measurement was performed by using the maximum possible rotation speed. The obtained cationized cellulose was first dissolved in deionized water as a 2 wt-% solution. Then, sodium chloride (NaCl) was added with a NaCl:cellulose weight ratio of 5:1, dissolved under mixing, and then the salt viscosity was measured. This means that the salt viscosity of the cationized cellulose was measured in a 1.8 wt-% concentration of a cationized cellulose aqueous solution (containing 9.1 wt-% NaCl). Cationized cellulose sample A has a 2% salt viscosity of 5700 mPas.
[0056] Conductivity
[0057] The conductivity of 0.5 wt-% cationized cellulose in deionized water was measured using a Knick SE 204 sensor. Cationized cellulose sample A had a conductivity of 0.51 mS / cm.
[0058] High shear processing
[0059] The high shear treatment was applied by mixing the cationized cellulose solution at 16000 rpm for 3-4 minutes using an Ultra-Turrax IKA T 25 D homogenizer with blades S 25 N - 25 F until the solution was slightly warmed. In order to define the coefficient of viscosity increase measured with 2% salt viscosity, the high shear treatment was carried out at a concentration of 2 wt-%. These conditions were then used for the high shear treatment at the process concentrations of the examples.
[0060] Application Example 2: Sludge Dewatering
[0061] Sludge dewatering tests were performed using the capillary suction time (CST) test using a Triton Model 319 Multipurpose CST (Triton Electronics Ltd, UK) with a Model 317 Agitator-Timer (Triton Electronics Ltd, UK).
[0062] In the CST test, the mixing speed was 1000 rpm. The diameter of the cylinder used was 18 mm. 0.2 wt-% cationized cellulose in solution was added to 100 g of digested sludge and mixed for 10 s after addition. After mixing for 10 s, 4.5 ml of the sample was taken out into the cylinder and the CST value was measured.
[0063] Digested sludge was collected from the Finnish sewage treatment plant. Before CST testing, the sludge was diluted with tap water to a dry content of 3.1%. Without the addition of any chemicals, the sludge gave a CST time of 452 s.
[0064] The cationized cellulose sample A from Example 1 was used in the experiment. The cationized cellulose was used (1) as it was after dissolution, or (2) after high shear treatment. The 2% salt viscosity of the cationized cellulose sample A was (1) 5700 mPas as it was after dissolution; and (2) 84000 mPas after high shear treatment. Thus, the salt viscosity of the cationized cellulose increased 14.7 times.
[0065] The CST results are shown in Table 1. High shear treated samples are indicated by "+UT". For the CST test, high shear treatment was performed at a concentration of 0.2 wt-%.
[0066] The results in Table 1 clearly show that high shear treatment of cationized cellulose improves the dewatering performance.
[0067] Table 1. CST time results of Application Example 2.
[0068] Dose [kg / t]* Sample A Sample A + UT 6 29.3 17.4 10 15.3 12 14 11 9.9 18 9.3 9.1
[0069] *Given in kg / tonne dry sludge
[0070] Application Example 3: Sludge Dewatering
[0071] Using the same principles as described in Example 1, various cationized celluloses were prepared from different cellulose starting materials. When the cationized celluloses were subjected to high shear treatment in the same manner as in Application Example 2, their viscosity increased significantly, which can be seen as an increase in their 2% salt viscosity values. The starting materials and properties of the cationized celluloses are given in Table 2. These properties were determined in the manner described in Example 1.
[0072] Table 2 Cationized cellulose used in Application Example 3.
[0073] sample Starting Materials Conductivity [mS / cm] Charge density [meq / g] 2% salt viscosity [mPas] 2% salt viscosity after UT* [mPas] coefficient Sample C High molecular weight dissolving pulp 0.66 2.7 726 1515 2.1 Sample D High molecular weight dissolving pulp 0.54 2.0 4409 > 100000 > 22.7
[0074] *Measured after high shear treatment
[0075] The CST test was performed as described in Example 2. Digested sludge was collected from the Finnish sewage treatment plant. Before the CST test, the sludge was diluted with tap water to a dry content of 3.6%. Without the addition of any chemicals, the sludge gave a CST time of 509 s.
[0076] The CST results are shown in Table 3. The high shear treated samples are indicated by "+UT". The results in Table 3 clearly show that high shear treatment improves the performance of cationized cellulose in liquid-solid separation. The CST time of the high shear treated cationized cellulose is lower at each dosage compared to the corresponding cationized cellulose without high shear treatment.
[0077] Table 3. CST time results of Application Example 3.
[0078] Dose [kg / t]* Sample C Sample C + UT Sample D Sample D + UT 8 34.4 26 37.2 22 12 14.8 13.3 17.3 13.6 16 10.8 9.9 10.5 10.5 20 9.1 8.7 10.8 9.9
[0079] *Given in kg / tonne dry sludge
[0080] Even though the invention has been described with reference to what currently appear to be the most practical and preferred embodiments, it should be understood that the invention should not be limited to the embodiments described above, but that the invention is also intended to cover different modifications and equivalent technical solutions within the scope of the appended claims.
Claims
1. A method for flocculating solid particles in a liquid-solid separation process, the method comprising: - obtaining a cationized cellulose having a charge density of at least 1.5 meq / g dry matter measured at pH 4 and a 2% salt viscosity of at least 50 mPas; - subjecting the cationized cellulose at process concentration to a process shear force in a high shear step, wherein the process shear force corresponds to or is greater than a default shear force that increases the 2% salt viscosity of the cationized cellulose by at least 2 times; - contacting the cationized cellulose with a suspension of solid particles suspended in a continuous aqueous phase after the high shear step and flocculating the solid particles; and - Separating the flocculated solid particles from the continuous aqueous phase in a dewatering step.
2. The method according to claim 1, characterized in that The cationized cellulose is in the form of a solution.
3. The method according to claim 1 or 2, characterized in that: The cationized cellulose is subjected to the process shear force in the high shear step corresponding to the default shear force which increases the 2% salt viscosity by 2-50 times, preferably 2-40 times, more preferably 5-30 times.
4. The method according to claim 1, 2 or 3, characterized in that: Prior to the high shear step, the obtained cationized cellulose is diluted to the process concentration.
5. The method according to any one of the preceding claims 1 to 4, characterized in that The process concentration is in the range of 0.1-5 wt-%, preferably 0.15-3 wt-%, more preferably 0.2-1 wt-%.
6. The method according to any one of the preceding claims 1 to 5, characterized in that The cationized cellulose has a 2% salt viscosity of at least 80 mPas, preferably at least 100 mPas, more preferably at least 150 mPas.
7. The method according to any one of the preceding claims 1 to 6, characterized in that The cationized cellulose has a turbidity of less than 1000 NTU, preferably less than 500 NTU, more preferably less than 250 NTU.
8. The method according to any one of the preceding claims 1 to 7, characterized in that The cationized cellulose has a degree of substitution DS of at least 0.32, preferably at least 0.37, more preferably at least 0.
4.
9. The method according to claim 8, characterized in that The cationized cellulose has a degree of substitution DS in the range of 0.32-1.75, preferably 0.37-1.6, more preferably 0.4-1.
5.
10. The method according to any one of the preceding claims 1 to 9, characterized in that The cationized cellulose has a charge density in the range of 1.5-4 meq / g dry matter, preferably 1.75-3.75 meq / g dry matter, more preferably 2-3.5 meq / g dry matter.
11. The method according to any one of the preceding claims 1 to 10, characterized in that The liquid-solid separation process is a wastewater treatment process, preferably municipal wastewater or industrial wastewater.
12. The method according to any one of the preceding claims 1 to 11, characterized in that The suspension has a biological oxygen demand (BOD) of > 50 mg / l, and / or a chemical oxygen demand (COD) in the range of 15-45 g / l, preferably 20-40 g / l, and / or a dry solids content in the range of 5-80 g / l, preferably 10-60 g / l, more preferably 20-55 g / l.
13. The method according to any one of the preceding claims 1 to 12, characterized in that The cationized cellulose is contacted with the suspension in an amount of 1-30 kg / ton of dry suspension, preferably 2-20 kg / ton of dry suspension, more preferably 3-15 kg / ton of dry suspension.
14. The method according to any one of the preceding claims 1 to 13, characterized in that The cationized cellulose is subjected to the process shear forces in a homogenizer, in a high-speed mixer, in a disperser, in a rotor-stator mixer, in a mixer with two counter-rotating rotors, in a centrifugal pumping device providing a straight or post-rotating flow, or in a shear pump.
Citation Information
Patent Citations
Method for producing cationized cellulose and cationized cellulose
CN114746452A
Manufacture of paper and paperboard
CN1387598A
Process for obtaining cationic cellulose microfibrils or their soluble derivatives as well as celluloses obtained by this process
EP0859011A1
Flocculation processes
US4943378A